Ion Beam Analysis - Development and Application of Nuclear Reaction Analysis Methods, in particular at a Nuclear Microprobe - Sjöland, K Anders (Nuclear Physics (Faculty of Science), 1996)
This thesis treats the development of Ion Beam Analysis (IBA) methods, principally for the analysis of light elements at a nuclear microprobe (NMP). The light elements are in this context defined as those with an atomic number Z of less than approximately 13 (aluminium). The work reported is to a large extent based upon multiparameter methods. Several signals are acquired simultaneously, and the data can be effectively analyzed to reveal structures that cannot be observed through one-parameter collection. Hydrogen analysis is performed through the H(p,p)H reaction, where the two protons are measured in coincidence at 45o. A specially designed annular silicon surface barrier detector (SBD) that is devided into two halves is used for the proton detection. This is a forward scattering technique, which requires thin samples. Lithium is measured through the 7Li(p,a)a reaction, where the two a particles are ejected almost back-to-back. This is utilised so that the two a particles are detected in coincidence by two annular SBDs, one in the forward direction and one in the backward direction. Two different set-ups for macro- and microanalysis is reported. The technique is applied to the analysis of Li drugs. The reaction used for boron analysis is the broad resonance at 662 keV of 11B(p,a)8Be*, 8Be* -> a + a; any of the a particles can be used for analysis. The technique is applied to Boron Neutron Capture Therapy (BNCT). The 19F(p,a)16O*, 16O* (0+) -> 16O (0+) + e- + e+ (internal pair production) is used for fluorine analysis. Any of the electron or positron is detected in coincidence with the a particle in order to suppress the background of the a particle. The technique is applied to problems related to odontology. To perform STIM (Scanning Transmission Ion Microscopy) at high beam currents, off-axis STIM is used so that STIM and the techniques for elemental analysis can be performed simultaneously. The above mentioned techniques are, by the work reported in this thesis, combined in a new set-up at the Lund Nuclear Microprobe. The various detectors for reaction products are arranged in such a way that they can be used for the simultaneous analysis of hydrogen, lithium, boron and fluorine together with traditional PIXE (Particle Induced X-ray Emission) analysis and STIM as well as pNRA (photon-tagged Nuclear Reaction Analysis). Finally, a technique to reject pile-up pulses and defective tail pulses from surface barrier detectors by the use of pulse shape discrimination (PSD) is demonstrated.
Keywords: ION BEAM ANALYSIS; HYDROGEN ANALYSIS; LITHIUM ANALYSIS; BORON ANALYSIS; FLUORINE ANALYSIS; BNCT; PSD; AFFECTIVE DISORDER; STIM; NRA; PIXE; SURFACE BARRIER DETECTORS; pNRA; Kärnfysik; Nuclear physics; DEPTH PROFILING; NUCLEAR MICROPROBE; PILE-UP REJECTION; Fysicumarkivet A:1996:Sjöland